Pengampunan Dosa dan Keselamatan Pada Masa Intertestamental dan Relevansinya Pada Masa Perjanjian Baru - Tawuru May, Farida (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2024)
The Intertestamental Period, lasting approximately 400 years between the Old and New Testaments, is often referred to as the "400 Silent Years" due to the absence of new divine revelations. This period, coinciding with the Second Temple era (530 BC–70 AD), raises critical theological questions, including the understanding of atonement and salvation among the Jewish people and the continuity of God's redemptive work leading to Jesus Christ. Using a library research method, this study explores the theological significance of this era as a bridge between the two testaments. Despite the Babylonian exile and the destruction of Solomon’s Temple, Jewish worship persisted through synagogues, and the Torah remained foundational. The promise of a Savior and the hope of deliverance endured, providing a crucial connection between Old Testament theology and its fulfillment in the New Testament message of salvation through Christ.